Torri, portici, logge nelle residenze venete di campagna pre-palladiane - Battilotti, Donata (Opus Incertum, 2016)
The country residences which were built in Veneto during the 14th and 15th centuries are more numerous than one may believe,and offer varying forms and typologies, both concerning the manors themselves, and in relation to the agricultural structuresattached to them. They were evolved from various medieval models, both urban and rural, which then branched into manydirections that, however, are for the most part ascribable to certain clearly defined typologies. The detailed survey carried outby the Regional Institute for Venetian Villas in 2006 permits a large scale analysis which identifies as well the constants andparticularities that are linked to the different geographic and cultural areas in the region.